The current decline of tropical marsupials in Australia: is history repeating?. Issue 2 (7th June 2013) - Fisher, Diana O.; Johnson, Chris N.; Lawes, Michael J.; Fritz, Susanne A.; McCallum, Hamish; Blomberg, Simon P.; VanDerWal, Jeremy; Abbott, Brett; Frank, Anke; Legge, Sarah; Letnic, Mike; Thomas, Colette R.; et al.
Abstract Aim A third of all modern (after 1500) mammal extinctions (24/77) are Australian species. These extinctions have been restricted to southern Australia, predominantly in species of 'critical weight range' (35–5500 g) in drier climate zones. Introduced red foxes (Vulpes vulpes) that prey on species in this range are often blamed. A new wave of declines is now affecting a globally significant proportion of marsupial species (19 species) in the fox‐free northern tropics. We aim to test plausible causes of recent declines in range and determine if mechanisms differ between current tropical declines and past declines, which were in southern (non‐tropical) regions. Location Australian continent Methods We used multiple regression and random forest models to analyse traits that were associated with declines in species range, and compare variables associated with past extinctions in the southern zones with current tropical (northern) declines. Results The same two key variables, body mass and habitat structure, were associated with proportion‐of‐decline in range throughout the continent, but the form of relationships differs with latitude. In the south, medium‐sized species in open habitats of lower rainfall were most likely to decline. In the tropics, small species that occupy open vegetation with moderate rainfall (savanna) are now experiencing the most severe declines. Throughout the continent, large‐bodied species and those in structurally complex habitats (rainforest) are secure. Main conclusions Our results indicate that there is no mid‐sized 'critical weight range' in the north. Because foxes are absent from the tropics, we suggest that northern Australian marsupial declines are associated with predation by feral cats (Felis catus) exacerbated by reduced ground level vegetation in non‐rainforest habitats. To test this, we recommend experiments to remove cats from some locations where tropical mammals are threatened. Our results show that comparative analysis can help to diagnose potential causes of multi‐species decline.